2004
DOI: 10.1111/j.1447-0756.2003.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of endometrial polyps detected hysteroscopically in eumenorrheic infertile women

Abstract: Diagnostic hysteroscopy should be used routinely in the work-up of infertile woman, even in the presence of eumenorrhea. Persistent functional endometrial polyps, even if small, are likely to impair fertility in this select patient group. Removal of such lesions may improve subsequent reproductive performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
87
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(94 citation statements)
references
References 13 publications
1
87
1
5
Order By: Relevance
“…so hysteroscopy is highly valuable and should be applied to all such patients especially with failed ICSI. [18][19][20] Fatemi et al) and Karayalcin et al demonstrated that uterine cavity abnormalities in their study population were low (11% for the 1st one and 22.9% for the 2nd one) while Gaviño-Gaviño et al found very high incidence of uterine pathology in their studies (64%) with repeated IVF failure. [21][22][23] Despite these drawbacks of non-using hysteroscopy before ICSI, many IVF clinics were reluctant in use of hysteroscopy for uterine cavity evaluation for difficulty or cost.…”
Section: Discussionmentioning
confidence: 96%
“…so hysteroscopy is highly valuable and should be applied to all such patients especially with failed ICSI. [18][19][20] Fatemi et al) and Karayalcin et al demonstrated that uterine cavity abnormalities in their study population were low (11% for the 1st one and 22.9% for the 2nd one) while Gaviño-Gaviño et al found very high incidence of uterine pathology in their studies (64%) with repeated IVF failure. [21][22][23] Despite these drawbacks of non-using hysteroscopy before ICSI, many IVF clinics were reluctant in use of hysteroscopy for uterine cavity evaluation for difficulty or cost.…”
Section: Discussionmentioning
confidence: 96%
“…17 Endocervical polyps were detected in 4.62% infertile patients and endometrial polyps were diagnosed in both primary and secondary infertility groups with a combined jsafoms incidence of around 8% (Table 4). The probable role and incidence of endometrial polyps in infertile patients is not clear as most of them remain clinically asymptomatic, but Shokeir et al 18 reported endometrial polyps in 16% of their infertility cases and found such lesions to be more common in the unexplained infertility group. They also reported a 50% pregnancy rate after hysteroscopic polypectomy, confirming the adverse role of endometrial polyps in causing infertility.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study of 224 infertile women who underwent hysteroscopy observed a 50% pregnancy rate after polypectomy. 12 Another study by Hinckley et al who did hysteroscopy in 1000 cases and found that 22% had endometrial polyp and concluded that a significant percentage of patients had uterine pathology detected by routine hysteroscopy that may impair the success of fertility treatment. 13 In our study out of 93 abnormal cases in laparoscopy interventions were done in 51 cases and out of 108 abnormal cases in hysteroscopy interventions were done in 49 cases.…”
Section: Discussionmentioning
confidence: 99%